Building rhetorical thinking At Ali Ibn Abi Talib and Al-Hasan - Halawani, Mariah Mohammed; Abu Bakr, Hani Farraj Ali (Arab Journal for Sciences and Research Publishing, 2022)
The Purpose of the study: The aim of the study was to highlight the construction of practical rhetorical thinking in the concepts of rhetoric by Imam Ali: `Rhetoric outlines ambiguities and reveals the defects of ignorance, in the simplest form of terms. While for Hussein, “rhetoric is the disclosure of statement of Mysterious wisdom, and an explanation of an issue”, “rhetoric is the distant approximation of wisdom in the simplest terms, by assuming that these concepts are linked to deduction, indications, and evidences. To discover the aspects of rhetoric and rhetorical deduction in these concepts and the extent to which, rhetoric is related to them, in terms of inference issues, understanding and comprehension. The study attempts to answer the question of whether the limit of the term rhetoric in the first generation includes the meaning of argument, influence and guidance through accomplishing and brevity. Methodology: the scientific method been utilised, through building on previous established knowledge, assuming that the concept of rhetoric since the first pioneer, are considered as eloquent, precious and comprehensive, solves problems and reveals new facts, eliciting that rhetoric is what the human mind require; wisdom, knowledge and experience. Themes: the point of the rhetoric limits from (Ali and Al-Hussien) view-points, in terms of reasoning, understanding, standards of comprehension and understanding, and related interpretive aspects of it. How to read it through seeing the graphic cognitive system, linking issues of comprehension, persuasion, and influence. Besides, the Rhetorical functions and related understanding, clarity, conviction, and inferring and deducing techniques of meanings. Results: The results indicated that the concepts of rhetoric showed that the building of thinking has an integrated comprehensive conception, which aids in solving problems by clarifying the ambiguous meaning, revealing the knowledge cache, examining and explaining it with the appropriate easy, concise, and eloquent way. As the Rhetoric is an integrated, practical, intellectual approach, in an effectual conscious language.